Trends in tissue repair and regeneration - Galliot, B. (2017)
The 6th EMBO conference on the Molecular and Cellular Basis of Regeneration and Tissue Repair took place in Paestum (Italy) on the 17th-21st September, 2016. The 160 scientists who attended discussed the importance of cellular and tissue plasticity, biophysical aspects of regeneration, the diverse roles of injury-induced immune responses, strategies to reactivate regeneration in mammals, links between regeneration and ageing, and the impact of non-mammalian models on regenerative medicine. © 2017. Published by The Company of Biologists Ltd.